The effect of different adipose tissue measurements on clinical prognosis in bladder cancer patients undergoing radical cystectomy: preliminary results. - Demirci, Aykut; Aydın, Hasan (Abdominal Radiology, 2025)
Purpose: Obesity has been linked to an increased incidence of various cancers, including bladder cancer. Among the different types of adipose tissue, visceral fat is recognized as the most metabolically active. However, there is a notable scarcity of studies investigating the impact of fat distribution, as measured by computed tomography (CT), on the prognosis of bladder cancer patients undergoing radical cystectomy (RC). Materials and methods: Between January 2013 and January 2024, preoperative CT images of 34 patients who underwent RC were analyzed to measure total perivesical fat area (TPFA, mm²), fat density (FD, %), and subcutaneous fat thickness (SFT, mm). Multivariate Cox regression analysis was used to assess the effects of these variables on prognosis. Results: The median age (IQR) of the patients was 65.5 years (12.5), and the median BMI (IQR) was 26.05 (5.98) kg/m². The median follow-up period (IQR) was 11 (31.2) months. A positive correlation was observed between BMI, TPFA, and SFT (r = 0.39, p = 0.02; r = 0.69, p < 0.001, respectively). According to Cox regression analysis, SFT, T stage, and N stage were found to be predictive factors for progression (HR = 1.11, p = 0.007; HR = 4.01, p = 0.04; HR = 6.47, p = 0.02, respectively), and T stage was also identified as an independent predictor for overall survival (HR = 5.32, p = 0.04). Conclusion: SFT measurement alongside clinical staging would be beneficial in determining progression following RC. Future randomized controlled trials supporting our findings will highlight the significance of these measurements.